A framework for risk assessment of cloud digital archives. Issue 1 (January 2018) - Hua, Xu; Sixin, Xue
Abstract : The credibility of cloud digital archives determines the security and evidence of archives digital resources. Based on the research significance of risk assessment, the authors analyse the ecological environment and the risk factors associated with cloud digital archives and propose a framework and key content for risk assessment. This study provides a foundation for building a risk assessment system for cloud digital archives.